2008
DOI: 10.1007/s10597-008-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

The Graduated Recovery Intervention Program for First Episode Psychosis: Treatment Development and Preliminary Data

Abstract: The Graduated Recovery Intervention Program (GRIP) is a novel cognitive-behavioral therapy program designed to facilitate functional recovery in people who have experienced an initial episode of psychosis. In this paper, the treatment development process of GRIP is described and data from an open feasibility trial are presented. Findings suggest clinical and psychosocial benefits associated with GRIP, and the treatment was well-received by clients and therapists. The retention rate of 67%, however, suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…Seven of the articles showed mental health nurses to play an important role in psychosocial interventions aimed to support the social functioning of the patient (Gillam, 2002;Linszen et al, 1998;Meulenbroeks et al, 1998;Renwick et al, 2009;Roks, Sebregts, Roza, & Jansen, 2008;Sousa, 1998;Waldheter et al, 2008). The psychosocial interventions involved: life and social skills training, psycho-education, and/or coping abilities training.…”
Section: Enhanced Social Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of the articles showed mental health nurses to play an important role in psychosocial interventions aimed to support the social functioning of the patient (Gillam, 2002;Linszen et al, 1998;Meulenbroeks et al, 1998;Renwick et al, 2009;Roks, Sebregts, Roza, & Jansen, 2008;Sousa, 1998;Waldheter et al, 2008). The psychosocial interventions involved: life and social skills training, psycho-education, and/or coping abilities training.…”
Section: Enhanced Social Functioningmentioning
confidence: 99%
“…Waldheter and colleagues (2008) report significantly positive results of CBT conducted on an individual basis on symptom improvement, particularly for positive symptoms (i.e., delusions or hallucinations), adaption to illness, and increased quality of life. Given the documented potential of CBT, researchers have called for integration of CBT into the treatment services provided for early psychosis (see Waldheter et al, 2008). According to Sin et al (2009b) and Rogers (2006), mental health services and mental health nurses should work to help people with mental health problems gain access to local employment and educational and occupational opportunities as part of the 2009 NICE guidance for schizophrenia.…”
Section: Enhanced Social Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Con el fin de conseguir esta óptima recuperación de los primeros episodios de psicosis en la última década se han ido desarrollando una serie de nuevas intervenciones psicologicas: Terapia de Orientación Cognitiva para el Primer Episodio de Psicosis (COPE) (Henry, Edwards, Jackson, Hulbert y McGorry, 2002); Terapia Cognitiva Interpersonal para la Recuperación y Prevención de Recaidas (Gumley y Schwannauer, 2006); Intervención para la Recuperación Cognitiva (CRI) (Jackcson et al, 2009); Terapia Cognitivo Conductual para la Recuperación Social de la Psicosis (SRCBT) (Fowler et al, 2009); Programa de Intervención para la Recuperación Gradual de la Psicosis Temprana (GRIP) (Waldheter et al, 2008); Terapia Cognitivo conductual para la Prevención de Recaída (RPT) (Gleeson et al, 2009).…”
Section: Nuevas Propuestas De Intervención En Psicosisunclassified
“…Following a thorough treatment development period (i.e., writing of the manual; obtaining feedback from clients, clinicians, and researchers; revising the manual) (Waldheter et al, 2008), we conducted an open-trial of GRIP with 10 individuals with first episode psychosis. Qualitative feedback and ratings indicated that GRIP was well-received by clients and clinicians, and it was associated with reduced positive symptoms at post-treatment (Waldheter et al, 2008).…”
Section: Introductionmentioning
confidence: 99%